Human papillomavirus independent status on pathologic response and outcomes in locally advanced cervical cancer managed with chemoradiotherapy followed by surgery. Issue 4 (31st January 2023) - Turco, Luigi Carlo; Pedone Anchora, Luigi; Fedele, Camilla; Inzani, Frediano; Piermattei, Alessia; Martini, Maurizio; Volpe, Mariaconcetta; Marchetti, Simona; Santangelo, Rosaria; Bizzarri, Nicolò; Cosentino, Francesco; Vargiu, Virginia; et al.
Abstract : Objective: While human papillomavirus (HPV) has been shown to play a significant role in cervical cancer carcinogenesis (HPV associated cases), a considerable percentage of cervical cancers occur independently of HPV status (HPV independent). Methods: In this retrospective study of 254 locally advanced cervical cancer patients treated with chemoradiotherapy and radical surgery, HPV genotypes were determined using the Anyplex II HPV28 kit that uses multiplex, real time polymerase chain reaction technology. The primary endpoints of this study were to evaluate the complete response to chemoradiotherapy (pathologic complete response), the presence of microscopic (< 3 mm, pathologic micro partial response, group 1) and macroscopic (>3 mm, pathologic macro partial response, group 2) residual carcinoma in the cervix, and the persistence of metastatic lymph nodes (group 3) in HPV independent cervical cancers. Secondary endpoints were evaluation of disease-free survival and overall survival. Results: Of 254 patients studied, 21 cases (8.3%) of cervical cancer were determined to be HPV independent. The percentage of pathologic complete response was found to be higher in the HPV associated group compared with the HPV independent group (p<0.001). In the HPV associated cervical cancer group, 5 year disease free survival was found to be 80.8% versus 59.9% in the HPV independent group (p=0.014). Overall survival was also higher in the HPV associated group (87.9%) compared with the HPV independent patients (69.4%) (p=0.023). In the multivariate analysis, the International Federation of Gynecology and Obstetrics (FIGO) stage and HPV genotypes maintained their relevant impact on pathologic complete response to chemoradiotherapy: FIGO stages IIIC1 and IIIC2 were associated with a 13-fold increased risk for the presence of metastatic lymph nodes compared with group 1 (p<0.001). HPV independent cervical cancers showed the highest risk for the development of macroscopic/stable disease (p=0.007), and persistence of metastatic lymph nodes (p=0.004) versus group 1, respectively. Conclusions: This study showed that HPV status at diagnosis could be a relevant factor for clinical outcomes in locally advanced cervical cancer patients.